Sikap Mahasiswa Prodi Pendidikan Khusus Terhadap Pendidikan Inklusif dan Kesiapan Belajar Bersama Penyandang Disabilitas di Universitas Negeri Makassar - Triyanto Pristiwaluyo; Purwaka Hadi; Wizerti Ariastuti Saleh (Seminar Nasional LP2M UNM, 2022)
Abstrak. The problems studied in this research are students' attitudes towards inclusive education and readiness to take part in joint education with persons with disabilities on campus. The research objective was to examine students' attitudes towards inclusive education and students' readiness to participate in co-education with persons with disabilities on campus. The variables in this study are students' attitudes towards inclusive education and readiness to participate in co-education with persons with disabilities. Data was collected using a questionnaire in the Google form format, which was distributed to all FIP students. The willingness of students to fill out the Google form was considered randomly. The number of students who filled out the questionnaire was 159 people. The data were processed using descriptive and correlation analysis techniques, with the help of the SPSS ready-to-use program. The results showed that all students had a positive attitude towards inclusive education, and there was no overall difference in attitudes towards inclusive education on campus between male and female students. Most of the students expressed their readiness to participate in co-education with persons with disabilities on campus. The attitude of students has a positive and significant relationship with the readiness of students to take part in education with persons with disabilities on campus. The experience of interacting with persons with disabilities has a positive and significant effect on students' attitudes toward persons with disabilities on campus. Kata Kunci: Persons With Disabilities, Inclusive Education, Student Attitudes